Stosowanie dorobku nauk o zarządzaniu w praktyce gospodarczej w opiniach przedsiębiorców i menedżerów. Kierunki, celowość, skuteczność - Lichtarski, Jan (Application of the Management Science Achievements in Practice in Entrepreneurs' and Managers' Opinions : Directions, Purposefulness and Effectiveness, 2006)
"The paper presents results of the research of entrepreneurs and managers opinions carried out in 80 big companies (corporations) in Poland in the following areas: real and expected range and directions of an organizational activity (including the implementation of the research results in the practice), its motives and barriers. This research includes also some features of the processes and results of changes. In the opinion mentioned above, the range and directions of changes which have take place so far are accepted, from the point of view of their rationality, purposes and effectiveness. Such approach leads to the next changes of the management systems within companies in the range which is similar to the past and current range of the corporate changes."
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 73-85